Pengaruh Penerapan e-SPT PPN Terhadap Efisiensi Pengisian SPT Menurut Persepsi Wajib Pajak: Survey Terhadap Pengusaha Kena Pajak Pada KPP Pratama â€œXâ€ - Ita Salsalina Lingga (Jurnal Akuntansi, 2012)
In order to improve the quality of tax services to the tax payer’s community, the Directorate General of Taxation implement electronic system(e-SPT) in reporting tax. The purpose of this research is to examine the influence on the implementation of e-SPT (Value Added Tax) towards efficiency of e-SPT filling. This research uses survey method with simple regression analysis. Data are collected through questionnaires which are distributed to tax payers at Bandung Tax Office. The conclusion of this research shows that the implementation of e-SPT (Value Added Tax) has a significant influence towards efficiency of e-SPT filling.